Increased index of microcirculatory resistance in older patients with heart failure with preserved ejection fraction - Xu, Zhuo (J Geriatr Cardiol, 2018)
OBJECTIVE: To study the coronary microvascular function in older patients with heart failure with preserved ejection fraction (HFpEF) using an invasive pressure–temperature sensor guidewire. METHODS: Patients undergoing echocardiography and cardiac catheterization examinations for exertional dyspnea and a positive stress test were retrospectively enrolled from January 2014 to November 2017, and were allocated into the control group or HFpEF group. The HFpEF group was secondary divided into two groups according to the age of 65. Comparing the clinical features and values obtained in examinations between the three groups, multivariate regression analysis was used to analyze the predictors of left ventricle end diastolic pressure (LVEDP). RESULTS: There were 87 patients enrolled in this study. The older HFpEF patients (n = 32) were more likely to be female; and had the most comorbidities, such as diabetes mellitus, atrial fibrillation, and chronic kidney dysfunction (CKD) with a low estimated glomerular filtration rate (eGFR), and had a similar hypertensive prevalence as the adult HFpEF group (n = 24), whose mean LVEDP and index of microcirculatory resistance (IMR) were highest in comparison to the adult HFpEF patients and controls (n = 31). The coronary flow reserve (CFR) in the older HFpEF and adult HFpEF groups was similarly reduced. In the regression analysis, the IMR linearly correlated to LVEDP, and was the only independent predictor of LVEDP. CONCLUSIONS: An increased IMR and reduced CFR were characteristics of microvascular dysfunction in older HFpEF patients. The IMR independently had a positive linear correlation with LVEDP. Microvascular rarefaction might be a subsequent pathological progression in the development of HFpEF.